2019
DOI: 10.1104/pp.19.00524
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Approaches to Improve Three Basic Plant Phenotyping Tasks Using Three-Dimensional Point Clouds

Abstract: Developing automated methods to efficiently process large volumes of point cloud data remains a challenge for threedimensional (3D) plant phenotyping applications. Here, we describe the development of machine learning methods to tackle three primary challenges in plant phenotyping: lamina/stem classification, lamina counting, and stem skeletonization. For classification, we assessed and validated the accuracy of our methods on a dataset of 54 3D shoot architectures, representing multiple growth conditions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 63 publications
1
32
0
Order By: Relevance
“…As shown in the middle of Figure 1, sometimes skeleton points do not lie within the enclosing boundary of the original point cloud data [27], [7]. This results in invalid geometry estimation of the input data.…”
Section: B Invalid and Inaccurate Geometry Estimation Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in the middle of Figure 1, sometimes skeleton points do not lie within the enclosing boundary of the original point cloud data [27], [7]. This results in invalid geometry estimation of the input data.…”
Section: B Invalid and Inaccurate Geometry Estimation Problemmentioning
confidence: 99%
“…Left: The problem of "zigzag" structure, where the skeleton does not follow the centerline of the stem and tends to deviate towards the branching point [15] (only the main stem skeleton is shown in the figure). Middle: The problem of biologically irrelevant skeleton points which falls beyond the boundary of the input data (shown at the top part), and inability to capture the geometric details for some branches [27], [7]. Right: Overlooking tiny geometrical structures [15].…”
Section: The Model a Curve Treementioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, 3D point cloud based analysis is getting extremely popular in phenotyping and agricultural applications (Vázquez-Arellano et al, 2016). Typical applications of point cloud based phenotyping include plant organ segmentation (Ziamtsov and Navlakha, 2019), robotic branch pruning (Chattopadhyay et al, 2016), automated growth analysis (Chaudhury et al, 2019), etc. Many of these applications require skeleton structure of the input point cloud data as a prior for further processing.…”
Section: Introductionmentioning
confidence: 99%
“…(Left) The problem of zigzag structure, where the skeleton does not follow the centerline of the stem and tends to deviate toward the branching point (Xu et al, 2007) (only the main stem skeleton is shown in the figure). (Middle) The problem of biologically irrelevant skeleton points which falls beyond the boundary of the input data (shown at the top part), and inability to capture the geometric details for some branches (Delagrange et al, 2014;Ziamtsov and Navlakha, 2019). (Right) Overlooking tiny geometrical structures (Xu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%